Czy Polska powinna pomóc Grecji? Relacja z debaty polityczno-ekonomicznej 2010-2012 - Kropiwnicki, Jerzy (Annales. Etyka w Życiu Gospodarczym, 2015)
This question raised emotions in Poland in 2010-2012. They began with the statementby the Prime Minister in March 2010 that Poland was ready to participate ina program of assistance to Greece. It evoked very strong reactions – not only indebates in conferences halls and in professional journals, but also in the tabloids andon TV and the radio. It was not only politicians and academic experts in economicswho took part in those debates, but also the editors of the popular newspapers.The arguments “for” and “against” of different character were raised. Those “for”advocated on the grounds of the principle of solidarity, but also on the grounds ofthe principle of subsidiarity – arguing that the burden of the problem is beyond thepossibilities of Greece to solve herself. They also raised the necessity to defend theendangered common good – the European Union, and argued that prudence advisesearning reciprocation in case Poland meets problems in the future. Those “against”pointed out that it was immoral to expect that a much poorer society was expected toassist one that was better off. Another point raised in the debate was that it was theGreeks themselves, both the political elites and the society as such, who were guiltyof creating Greece’s problems. The main problem was the institutions of the welfarestate, developed beyond the capacities of the country. But there were also somemore shocking reasons of the Greek economic problems – and among them massivetax-avoidance, unauthorized social benefits payments, and transfers of incomes toforeign bank accounts. There was also the manipulation of statistical data or eventheir falsification, by (or with the approval of) the government. Some participantsin the debate raised the problem Greek frauds and social dysfunctions being verywell known to the EU authorities, the partners of Greece in EMU and by the German and French commercial banks. So – following from the above – Poland should notparticipate in any programs of assistance to Greece, and the burden of the problemshould rest on those who had been responsible for it or who had tolerated its growthbecause of expected profits. In other words: Greek society, its political elites and thebanks and those countries that had tolerated the developments. The debate ended inPoland when the member-states of the EMU decided that they would take decisionsconcerning Greece within their own group. And it was decided that “troika” – representativesof the European Commission, ECB and IMF – would decide on the sizeof the assistance and of the conditions. Poland, as a member of the IMF, does in factparticipate in the costs of the assistance programs, but this fact does not evoke greatemotions.